PENGUKURAN KEMAMPUAN BERPIKIR KRITIS SISWA SMA MELALUI SOAL BERBASIS HOTS DAN IMPLIKASINYA PADA BIMBINGAN KONSELING - Ramadinah, Nadya; Mufatihah, Zahra; Putri Nur, Latiffa Amanda; Nadhifa, Dwi Erma; Minarsi, Minarsi (Jurnal Muria Research Guidance and Counseling (MRGC), 2025)
Critical thinking skills are essential in 21st-century education as they support problem solving, decision making, and reflective reasoning. This article analyzes the implementation of Higher Order Thinking Skills (HOTS)-based assessment as an evaluation tool to measure and improve critical thinking among senior high school students, along with its implications for guidance and counseling services. The method used is a literature review of related scientific publications. The findings indicate that students' critical thinking abilities remain at a low to moderate level, particularly in analysis, evaluation, and integration skills. Key challenges include teachers’ limited capacity to design valid instruments and students' lack of exposure to cognitively demanding tasks. One effective strategy for school counselors is to deliver classical guidance services using Problem-Based Learning (PBL), Self-Regulated Learning (SRL), and interactive media, which foster active engagement, independent learning, and the development of students’ critical and reflective thinking skills.